Aplikasi Bermain Finger Painting Terhadap Perkembangan Motorik Halus Pada Anak Prasekolah - Fitriani, Novita Fitriani; Mareta, Reni; Sulistyono, Dwi (Borobudur Nursing Review, 2022)
Introduction: Preschool children are early childhood aged between 3-6 years, where fine motor development is needed to support their readiness to optimize body movements that involve high accuracy, eye persistence and small muscles such as playing puzzles, mixing colors, drawing with fingers (finger painting). Finger painting is a game with techniques to develop expression, express imagination and creation by painting directly with the fingers without using tools. Finger painting can train the coordination of the muscles of the fingers and eyes, train the combination and combination of colors to make the beauty of the hand movements it does. Objective: This study aims to see the effectiveness of finger painting playing stimulation to improve fine motor skills in preschool age children as a preparation for children to enter the next level of education. Methods: This research is a case study using a purposive sampling method. The sample in this case study is An. M aged 5 years with the results of the developmental pre-screening questionnaire (KPSP) was dubious with the risk factors still having difficulty learning to draw well. The research data was taken using participatory observation methods, unstructured interviews, and documentation. After tabulating the existing data were analyzed using the analysis domain. Results: The results showed that the application of playing finger painting on the risk of developmental disorders experienced by An. M indicates an increase in fine motor development. This is indicated by the observation scores that were carried out pre-test and post-test which were carried out for 3 times in 3 days. Conclusion: The application of playing finger painting can be applied as a stimulation for children to improve fine motor development so as to overcome the problem of risk of developmental disorders. Keywords: Finger painting; Fine Motor Development; Preschool